Assessing the antitumor potential of variants of the extracellular carbohydrate polymer from synechocystis ΔsigF mutant - Mota, Rita (2023)
Cancer is a leading cause of death worldwide with a huge societal and economic impact. Clinically effective and less expensive anticancer agents derived from natural sources can help to overcome limitations and negative side effects of chemotherapy and radiotherapy. Previously, we showed that the extracellular carbohydrate polymer of a Synechocystis ΔsigF overproducing mutant displayed a strong antitumor activity towards several human tumor cell lines, by inducing high levels of apoptosis through p53 and caspase-3 activation. Here, the ΔsigF polymer was manipulated to obtain variants that were tested in a human melanoma (Mewo) cell line. Our results demonstrated that high molecular mass fractions were important for the polymer bioactivity, and that the reduction of the peptide content generated a variant with enhanced in vitro antitumor activity. This variant, and the original ΔsigF polymer, were further tested in vivo using the chick chorioallantoic membrane (CAM) assay. Both polymers significantly decreased xenografted CAM tumor growth and affected tumor morphology, by promoting less compact tumors, validating their antitumor potential in vivo. This work contributes with strategies for the design and testing tailored cyanobacterial extracellular polymers and further strengths the relevance of evaluating this type of polymers for biotechnological/biomedical applications.